Cytotoxic and molecular effects of betel quid and areca nut extracts on selected oral epithelial cell lines - Al-Tayar, Badr Abdullah Saeed (2022)
The habit of betel quid chewing is widely prevalent in many parts of Asia. Betel quid comprises areca nut, betel leaf, lime, and other potential constituents such as tobacco and essences. The main ingredient of betel quid is areca nut. Many epidemiological studies link betel quid and areca nut chewing to oral cancer. Therefore, this study aimed to investigate the effect of areca nut and betel quid on mouth-ordinary-epithelium1 (MOE1) and human oral squamous carcinoma (HSC-2). Phytochemical compounds were identified using GC–MS. MOE1 and HSC-2 cells were treated with high concentrations (25–100%) and low concentrations (0.0122– 25%) and subjected to MTT assay. The cell and nuclei morphological changes were observed under inverted phase contrast and fluorescence microscopes. Following microarray analysis, the gene expression data was subjected to bioinformatic analysis. Microarray data was validated by analysing the expression of six selected genes through real-time reverse transcription-quantitative polymerase chain reaction (RT-qPCR). Arecoline was identified as the major chemical compound in areca nut alkaloids, while phenol, 2 methoxy4 (1propenyl) was the major chemical compound in betel quid phenolics. MOE1 treated with areca nut decreased in viability starting from 0.0244% until 1.56%. However, at concentrations 6.25% and above, the cells viability increased. With betel quid treatment, MOE1, cell viability started to decrease at extract concentration of 0.78% (24 hours) and 3.125% (48 and 72 hours). However, at concentration 50% and 100%, the cell viability increased significantly. Areca nut treatment on HSC-2 decreased the cell viability tremendously at all concentrations and treatment time. Betel quid concentration from 6.25% to 25% decreased HSC-2 viability significantly at all treatment duration. Based on the cytotoxicity data, two concentrations were selected, which were 0.0976% for areca nut and 6.25% for betel quid for the subsequent experiments. Microscopy findings indicated that the extracts caused noticeable morphological changes such as cell shrinkage and ballooning, nuclei condensation, and fragmentation. The microarray gene expression analysis revealed that the total number of DEGs in MOE1 treated with areca nut and betel quid compared to controls was 3,038 and 1,985, respectively, while in HSC-2, it was 4,413 and 1,110, respectively. The shared upregulated DEGs of areca nut treatment were CLDN4, PIM1, and HBEGF. KEGG analysis suggested the genes are associated with few main pathways, including the ErbB signalling pathway. The shared upregulated DEGs for betel quid treatment are HMOX-1, GCLM, and EGLN3. Its KEGG analysis suggested an association with a few pathways, mainly ferroptosis. RT-qPCR results of selected genes validated the microarray gene expression. In conclusion, areca and betel quid showed different effects on normal and malignant epithelial cells, whereby cell survival mechanism might play an important role in cells treated with betel quid compared to the areca nut treatment.